Moxibustion (artemisia plant at acupuncture point) as alternative therapy in hypertension: a promising approach - Siddiqui, Mohammad Jamshed Ahmad; Kamarudin, Mohamad Fadly; Al Shami, Abdulkareem Mohammed; Mat So'ad, Siti Zaiton; Jamshed, Shazia Qasim (Wolters Kluwer, 2017)
Hypertension is a pathological condition in which the blood pressure is higher than under normal physiological conditions, i.e., 140/90 mmHg or higher. Blood pressure is measured as the force exerted by the blood pumped by the heart against the walls of arteries (aorta) and distributed throughout the body. Use of complementary and alternative medicine as a cure for hypertension is a common phenomenon because of the high risk of cardiovascular complications and kidney diseases caused by conventional Western medicine. It is reported that high blood pressure causes ~49% of myocardial infarction and 62% of strokes. Effective treatment of hypertension is restricted by adverse effects and cost of the medication. Moxibustion is the application of heat by burning a small bundle of tightly bound moxa, to targeted acupoint, and sometimes it is used along with acupuncture. Encouraging results have been reported on randomized trials indicating the ef cacy of moxibustion. But more controlled clinical trials are required to further establish the potential ef cacy of moxibustion approach in hypertension.